Descaminhos gerais: a representação do jagunço em Bernardo Élis - Ribeiro, Thiago Fernandes Soares (2011)
This work, General Unpaths: the jagunço's representation in Bernardo Élis, aims to study the ways in which the Goian author, Bernardo Élis, represents and configures the images of the jagunço in his novelistc discourse, O Tronco. In this sense, we tried, through a historical perspective, to find the literaries origins of this usual character in our Literature, mainly in the Brazilian Regionalism, and understand how she was utilized in bernardian writing.